Landslide susceptibility mapping in East Ungaran, Indonesia: A comparative study using statistical methods - Maulana, Deviana Shinta; Indrawan, I Gde Budi; Warmada, I Wayan (Journal of Degraded and Mining Lands Management, 2024)
East Ungaran, is one of landslide prone areas in Semarang Regency, Indonesia. In addition to provide a more detail map of landslide susceptibility, the objective of this research was to compare performance of three widely used methods, which are the Weight of Evidence (WoE), Logistic Regression (LR) and combined Weight of Evidence (WoE) – Logistic Regression (LR), for landslide susceptibility mapping. Slope, elevation, lithology, land use, normalized difference vegetation index (NDVI), distance from lineament, distance from river, and distance from road were considered as landslide controlling parameters in the research area and were used as input variables in the landslide susceptibility zonation. The results showed that the slope, elevation, and distance from the road are significant parameters causing the landslides. The research area is divided into very low, low, moderate, and high landslide susceptibility zones. The WoE performs better than the LR, while the combined WoE-LR method performs the best among the three methods in predicting landslide susceptibility in this area. The landslide susceptibility map developed using the combined WoE-LR method is suggested to be used for landslide mitigation planning of this area.